2021
DOI: 10.1515/dmpt-2021-0123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of reproductive hormones and their receptors in assisted reproduction technology for patients with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathies in women of childbearing, which is defined by the accumulation of multiple, small fluid-filled ovarian cysts without the selection of a single dominant follicle. Most PCOS phenotypes are characterized by the absence of spontaneous ovulation, resistance toward ovulation inductors, the production of a large immature oocytes number, and the high prevalence of ovarian hyperstimulation syndrome, resulting in reduced assisted reproductive te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…This surplus adipose tissue is thought to release a range of hormones and cytokines, such as estrogen and insulin-like growth factor 1 (IGF-1) [28,29]. The presence of these hormones may affect ovarian function by in uencing the production of estrogen in the local area, ultimately contributing to the onset of polycystic ovary syndrome (PCOS) [30]. Furthermore, a higher body mass index during childhood is indicative of a higher degree of insulin resistance [31].…”
Section: Discussionmentioning
confidence: 99%
“…This surplus adipose tissue is thought to release a range of hormones and cytokines, such as estrogen and insulin-like growth factor 1 (IGF-1) [28,29]. The presence of these hormones may affect ovarian function by in uencing the production of estrogen in the local area, ultimately contributing to the onset of polycystic ovary syndrome (PCOS) [30]. Furthermore, a higher body mass index during childhood is indicative of a higher degree of insulin resistance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that excessive androgen in PCOS patients can promote the recruitment and growth of follicles, producing a large number of small and immature follicles, eventually leading to polycystic changes in the ovary. Conversely, when the follicle diameter reaches 2~8 mm, the increased androgen will promote atresia [ 3 , 4 ]. At the same time, these small follicles also secrete excessive levels of anti-Mullerian hormone to inhibit the aromatase activity induced by follicle-stimulating hormone (FSH) and hinder follicular development.…”
Section: Introductionmentioning
confidence: 99%